2016
DOI: 10.1111/trf.13728
|View full text |Cite
|
Sign up to set email alerts
|

Technical comparison of four different extracorporeal photopheresis systems

Abstract: BACKGROUND Extracorporeal photopheresis (ECP) is a therapeutic technique that combines leukapheresis and ultraviolet (UV)A irradiation of the leukapheresate after 8‐methoxypsoralen treatment with subsequent retransfusion. It can be achieved with a single device (online) or by combining an apheresis machine with a separate UVA light source (offline). The comparability of both established methods is unknown. STUDY DESIGN AND METHODS In a prospective setting, four ECP systems were evaluated: one with integrated U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 22 publications
11
46
2
3
Order By: Relevance
“…We have observed higher nontargeted cells contamination in the Spectra Optia group. This is contradictory with previously published studies, which mainly reported larger granulocyte 13,[22][23][24] and red blood cell (RBC) contaminations 13,25 with the COBE Spectra device. Despite higher granulocyte contaminations in our Spectra Optia group, it remained lower than those reported by Del Fante et al 21 13 Even if most of the products showed a low granulocyte contamination (<30%), a total of 30 procedures showed an unusually high granulocyte contamination (>30%).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We have observed higher nontargeted cells contamination in the Spectra Optia group. This is contradictory with previously published studies, which mainly reported larger granulocyte 13,[22][23][24] and red blood cell (RBC) contaminations 13,25 with the COBE Spectra device. Despite higher granulocyte contaminations in our Spectra Optia group, it remained lower than those reported by Del Fante et al 21 13 Even if most of the products showed a low granulocyte contamination (<30%), a total of 30 procedures showed an unusually high granulocyte contamination (>30%).…”
Section: Discussioncontrasting
confidence: 89%
“…We have observed higher nontargeted cells contamination in the Spectra Optia group. This is contradictory with previously published studies, which mainly reported larger granulocyte and red blood cell (RBC) contaminations with the COBE Spectra device. Despite higher granulocyte contaminations in our Spectra Optia group, it remained lower than those reported by Del Fante et al (9.1 ± 16% on CMNC and 12.2 ± 19.1% on MNC) and within the range of Del Fante et al (3.8 (2.8‐6.4)%) for MNC products in 2013 .…”
Section: Discussioncontrasting
confidence: 88%
“…More importantly, our study with the long‐term follow‐up confirms that ECP causes no major side effects. Despite the lack of randomized studies comparing different ECP methods, it seems that the online method used in this study is safe in adult patients with lower hemoglobin values . It only requires frequent visits and central vein access that are either way necessary in patients suffering from severe aGVHD or extensive cGVHD.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the lack of randomized studies comparing different ECP methods, it seems that the online method used in this study is safe in adult patients with lower hemoglobin values. 28 It only requires frequent visits and central vein access that are either way necessary in patients suffering from severe aGVHD or extensive cGVHD. Although no head-to-head comparisons with other second-line agents are feasible, it should be noted that novel agents are continuously being studied in GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance of these findings is unclear. 16 Our group here at Children's National compared the two most frequently used instruments, the Uvar XTS and Cellex, by performing a retrospective analysis of 10 pediatric patients who have received ECP for SR-GVHD (both acute and chronic). Compared to the Uvar XTS1 instrument, use of the Cellex instrument resulted in shorter runtimes, increased percentage of mononuclear cells treated, reduced incidence of line occlusions requiring tissue plasminogen activator (TPA) treatment and decreased incidence of patient-related complications.…”
Section: Introductionmentioning
confidence: 99%